Long-range photoinduced charge separation in tröger bases D/A dyads - Dusso, Diego (2019)
Tröger´s base (and its derivatives) are compounds comprised of two aromatic (or polyaromatic) rings bridged by a diazocine aliphatic cycle. We report herein the photophysical properties of two series of novel Tröger´s bases (TB) asymmetrically substituted by electron donor (D) and electron acceptor (A) substituents. In TB series 3, a carbonitrile group (A[dbnd]CN) lies at the position 2 of the heterocycle, while position 8 is occupied by a series of D with increasing reductant capacity: H (3a), CH3 (3b), OCH3 (3c) or N(CH3)2 (3d). A novel TB series (5a-5d) which comprise the same D, but a 2,2-dicyanovinyl group (A = CHC(CN)2) as electron acceptor, was synthesized and fully characterized. TB absorption (νA max) and emission energies (νF max), fluorescence quantum yields (ΦF) and emission lifetimes (τF) were determined in a series of aprotic solvents covering a wide range of medium polarity (ε∼2-38). νF max, ΦF and τF largely depend on the polarity of the medium and the nature of D/A pair. From the solvatochromic study on νF max, it is concluded that upon excitation TB´s develop large degrees of charge separation (CT). Photophysically, 3a-3c resembles 4-(N,N-dimethylamino)benzonitrile derivatives showing internal CT state dipole moments (μ1 *) of ∼ 15–17 D. For 3d and the entire series 5, CT occurs throughout the diazocine ring giving rise to giant μ1 * (> 25 D). This is indeed an unusual result, because it strongly suggests that the aliphatic diazocine ring can couple the D/A redox centers as a π bridge would do.